THE CONTRIBUTION OF TEACHERS’ PERSONAL RELATIONSHIP AND THEIR PERCEPTION OF SUPERVISION IMPLEMENTATION TOWARD WORK ACHIEVEMENT MOTIVATION - Fitriadi Lubis (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2017)
The purpose of this research is to examine the relationship between teachers’ interpersonal relationship and their perception about supervision implementation and their contribution toward their work achievement motivation. The data were obtained from 55 teachers as the sample by stratified proportional random sampling. The data were analyzed by means of correlation and multiple regression technique. The results of this study show that the contribution of interpersonal relationship variable was 28% to work achievement. Meanwhile, the teachers’ perception of supervision implementation variable contributes 17% to work achievement motivation variable. The contribution of the two dependent variables was 41% to work achievement motivation variable.